Hush! : a Thai lullaby - Ho, Minfong; Meade, Holly (New York : Orchard Books, 1996)
A lullaby which asks animals such as a lizard, monkey, and water-buffalo to be quiet and not disturb the sleeping baby.
Wilson's Children
Elem. School Library Collection
Caldecott Medal/Honor
1.9
K-3
Keywords: Lullabies, American; Thailand -- Juvenile poetry; Lullabies; American poetry; Thailand -- Poetry; Lullabies; American poetry; Thailand -- Poetry